EVALUATION OF ANTIOXIDANT ACTIVITY LEVEL OF ACTINIDIA ARGUTA (SIEBOLD ET ZUCC.) PLANCH. EX MIQ. PLANT RAW MATERIAL, GROWN IN THE CAUCASIAN MINERAL WATERS REGION - D. I. Pozdnyakov; S. L. Adzhiakhmetova; N. N. Vdovenko-Martynova (Фармация и фармакология (Пятигорск), 2022)
The aim of the study is the identification and evaluation of a new antioxidant activity in a potentially new medicinal raw material of Actinidia arguta folia.Materials and methods. The total content of antioxidants was measured on a Tsvet Yauza-01-AA liquid chromatograph using the amperometric method. In parallel, the antioxidant activity of Actinidia arguta extracts was studied in vitro in the following dilution range: 62.5 µg/ml, 125 µg/ml, 250 µg/ml, 500 µg/ml and 1000 µg/ml. Herewith, DPPH, superoxide, and hydroxyl radical inhibitory properties of the analyzed samples were evaluated.The studies of the antioxidant activity with the determination of the activity of superoxide dismutase, glutathione peroxidase, catalase, the concentration of malondialdehyde and diene conjugates, have been conducted in vivo.Results. When studying the antiradical activity (in vitro tests), it was found out that the highest radical-inhibiting activity comparable to the individual compound - quercetin, has the extraction from Actinidia arguta folia, obtained by the extraction with 40% ethyl alcohol. The IC50 value for the given extract in relation to DPPH; superoxide and hydroxyl radical, amounted to 537.6±23.924 µg/ml; 26.6±2.627 µg/ml and 72.6±3.264 µg/ml, respectively, which may indicate that this extract has reducing and radical scavenging properties. In parallel, the study of the total content of antioxidants in terms of quercetin and gallic acid has been carried out. It has also been found out that in the Actinidia arguta folia extract, obtained by the extraction with 40% ethyl alcohol, the content of the antioxidants is maximum.Conclusion. The data obtained using the in vitro test were confirmed in the in vivo study, in which the course application of the Actinidia arguta folia extract, obtained by the extraction with 40% ethyl alcohol to the degree comparable to quercetin, contributed to an increase in the superoxide dismutase activity, a decrease in the lipid peroxidation products. The maximum content of antioxidants for Actinidia arguta folia was 0.73±0.007 and 0.47±0.005 mg/g in terms of quercetin and gallic acid, respectively. The extractant was 40% ethyl alcohol.